TREND AND PREVALENCE OF STUNTING IN CHILDREN UNDER TWO YEARS FROM 2007- 2016 IN CENTRAL SULAWESI - nasrul, nasrul; maudu, rusli; hafid, fahmi (Tadulako University, 2017)
Background & Objective: Trend and prevalence of stunting are required to see the success of communityhealth nutrition outcomes over time. The purpose of this research is to know the trend and stuntingprevalence in baduta year 2007, 2011 and year 2016 in Central Sulawesi. Material and Method : Thisresearch used a retrospective cohort design. This research is conducted on June 7, 2017 until October 3, 2017in Palu City and Donggala Regency Central Sulawesi. The population in this study was the data sets of PSGin 2007, 2011 and 2016 as much as 16,105. Samples were 6391 sets of data baduta. Results: Prevalence ofstunting in 2007, 2011 and 2016 was 32.3%, 31.5% and 26.0%, respectively. In the last 9 years there was a6.2% decline or an average of 0.6% per year. Conclusion: The prevalence of Baduta in 2007, 2011 and2016 consecutively was 32.3%, 31.5% and 26.0%. Prior programs that have been undertaken by the healthdepartment are continued by improving cross-sectoral cooperation in sensitive programs the first 1000 daysof life. The highest stunting problem in the 12-23 month age group means stunting prevention focuses onstrengthening the complementary feeding program.